AQUIFER TRANSMISSIVITY VALUES FROM VES FOR PARTS OF PORT HARCOURT, RIVERS STATE, NIGERIA - P.O, Eke; George F, Life (International Journal of Research -GRANTHAALAYAH, 2018)
This paper presents aquifer transmissivity values obtained from vertical electrical sounding method from some locations in Port Harcourt Local Government Area of Rivers State. Twelve (12) stations were occupied using the Schlumberger electrode configuration with maximum electrode spacing of 400 m. The data were interpreted using IPI2WIN software version 3.0.1 (2003).The results reveal four layer strata with transmissivity (Tr) values of between 145.53 and 18264.42 m2/day with average value of 7252.23 m2/day. These indicate high aquifer transmissivity values for the study area with high permeable and significant storability of the formations that enhances the migration and circulation of ground water within the region. The results indicate that the southern part of the study area is the most prolific in terms of groundwater exploitation and thus the most promising in sitting productive boreholes.